Effect of landscape design on depth perception in classical Chinese gardens: A quantitative analysis using virtual reality simulation - Zhu, Haipeng; Gu, Zongchao; Ohno, Ryuzo; Kong, Yuhang (Frontiers in Psychology, 2022)
It is common for visitors to have rich and varied experiences in the limited space of a classical Chinese garden. This leads to the sense that the garden’s scale is much larger than it really is. A main reason for this perceptual bias is the gardener’s manipulation of visual information. Most studies have discussed this phenomenon in terms of qualitative description with fragmented perspectives taken from static points, without considering ambient visual information or continuously changing observation points. A general question arises, then, on why depth perception can vary from one observation point to another along a garden path. To better understand the spatial experience in classical Chinese gardens, this study focused on variations in perceived depth among different observation points and aimed to identify influential visual information through psychophysical experimentation. As stimuli for the experiment, panoramic photos of Liu garden were taken from three positions at Lvyin Pavilion. Considering the effects of pictorial visual cues on depth perception, the photos were processed to create 18 kinds of stimuli (six image treatments * three positions). Two tasks were presented to the participants. In Task 1, 71 participants were asked to rate the depth value of the garden using the magnitude estimation method in a cave automatic virtual environment (CAVE). Statistical analysis of Task 1 revealed that depth values differed significantly among different viewpoints. In Task 2, participants were asked to compare 18 stimuli and 3D images presented on three connected monitors and to judge the depth of the garden using the adjustment method. The results of Task 2 again showed that depth values differed significantly among different viewpoints. In both tasks, ambient information (i.e., the perspective of interior space) significantly influenced depth perception.